CYBER PUBLIC RELATIONS MANAGEMENT IN THE ERA OF PUBLIC INFORMATIONS DISCLOSURE - Komariah, Kokom; Hamad, Ibnu; Sari, Yunita (Universitas prof. Dr. Moestopo (Beragama), 2025)
This research aims to analyze the implementation of Cyber ​​Public Relations (CPR) management in the era of public information openness with a case study at the DKI Jakarta Province Department of Industry, Trade, Cooperatives, Small and Medium Enterprises (PPKUKM). The research method used is qualitative with a case study approach. The theoretical framework used includes the Cyber ​​Public Relations management theory from Rosady Ruslan and the Cyber ​​Public Relations analysis theory from Philips & Young. Research data was obtained through in-depth interviews with CPR implementers, as well as observations of social media and related service websites. The results of the research show that the DKI Jakarta Provincial PPKUKM Service, as an informative public body that has met the indicators of public information openness, has utilized digital technology in managing CPR by implementing the planning, organizing, actuating and controlling stages. CPR implementation is carried out through various digital platforms with an omni-channel approach. This research also identifies challenges in packaging information and public communication strategies, especially in meeting the information needs of MSME actors. These findings provide recommendations for improving the delivery of information that is more relevant, targeted and has a positive impact on MSME entrepreneurs.